Implementation Model of Merdeka Belajar–Kampus Merdeka in Curriculum Management of Islamic Education Management Programs across Islamic Universities in Indonesia - Ahmad Salabi; Nauriatul Muharramah (Kharisma: Jurnal Administrasi dan Manajemen Pendidikan, 2026)
The purpose of this study is to analyze the implementation model of the Merdeka Belajar–Kampus Merdeka (MBKM) policy in the curriculum management of the Islamic Education Management (MPI) study program to meet the needs of Generation Z students. This research was motivated by the demands of the Industrial Revolution 4.0 era and the COVID-19 pandemic, which shifted the higher education paradigm and required students to become active creators of knowledge. The MBKM policy is positioned as an effort to strengthen students’ competencies and employability, which were previously constrained by lecturer-centered learning practices. This study employs a qualitative approach with research and development (R&D) methods, with empirical findings drawn from the implementation practices at UIN Sunan Kalijaga Yogyakarta. The results show that MBKM is implemented through curriculum restructuring, expansion of cross-program learning options, lecturer mobility, partnership-based learning, and flexible study pathways. Evaluation and monitoring are carried out using Outcome-Based Education (OBE) principles to ensure alignment with the learning characteristics of Generation Z students. The study concludes that the MBKM implementation model adopted in the MPI program at UIN Sunan Kalijaga effectively enhances curriculum adaptability, improves student autonomy, and strengthens competency-based learning. This model provides an empirically grounded framework that can be utilized and further adapted by other Islamic Higher Education institutions seeking to develop responsive and innovative curriculum management strategies.